2018
DOI: 10.9740/mhc.2018.05.116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating psychiatric outcomes associated with direct-acting antiviral treatment in veterans with hepatitis C infection

Abstract: Introduction:Approximately 70% of veterans with hepatitis C virus infection have at least one psychiatric illness. The advent of direct-acting antiviral (DAA) therapy provided an alternative to interferon-alpha regimens and revolutionized treatment, however, the extent of psychiatric effects attributed to these agents are unclear. The primary objective of this pilot study was to prospectively analyze psychiatric outcomes, specifically depression, in veterans with hepatitis C virus infection who are initiated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…These safety results of the psychiatric symptomatology corroborate those observed in previous studies, at the level of the evaluation on anxiety or depression, fatigue and mood, cognitive state, or sleep disturbances 56‐60 . In addition, patients with psychiatric disorders, in this study, have not developed decompensation of their mental illness during DAAs treatment, as other authors have also evaluated but limited to DAAs treatments based on ribavirin 61 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These safety results of the psychiatric symptomatology corroborate those observed in previous studies, at the level of the evaluation on anxiety or depression, fatigue and mood, cognitive state, or sleep disturbances 56‐60 . In addition, patients with psychiatric disorders, in this study, have not developed decompensation of their mental illness during DAAs treatment, as other authors have also evaluated but limited to DAAs treatments based on ribavirin 61 …”
Section: Discussionsupporting
confidence: 89%
“…[56][57][58][59][60] In addition, patients with psychiatric disorders, in this study, have not developed decompensation of their mental illness during DAAs treatment, as other authors have also evaluated but limited to DAAs treatments based on ribavirin. 61 T A B L E 5 Multivariate analysis on SVR12…”
Section: The Importance Of Adherence To Antiviral Treatment Based Onmentioning
confidence: 99%
“…They reported that anxiety and depression scores did not change during the follow-up period (treatment period and 12 weeks after). In a study sample of veterans with and without mental health diagnosis, there was no change in depression scores evaluated by the Patient Health Questionnaire, from baseline to end of the treatment (22). No psychiatric decompensation was reported while using DAA in that study.…”
Section: Introductionmentioning
confidence: 62%
“…The low number of participants and the prevalent diagnosis of mixed anxiety-depressive disorders did not allow us to analyze further the differences among subgroups with other psychiatric diagnoses. Previous studies centered mainly on patients with major depressive disorders and substance abuse or dependence [12,35]. Furthermore, the advanced liver disease in some patients, the relevant comorbidities, and no patients with HIV co-infection might act as impeding factors for achieving the generalizability of our results.…”
Section: Discussionmentioning
confidence: 93%
“…Yet, differences exist in the design, sample, and size of the study, clinical and time evaluation, severity and definition of psychopathological symptoms, plus the use of self-reported or observer-rated diagnostic interview scales [29][30][31][32][33][34]. According to a few studies [12,[35][36][37][38], DAA therapy is safe and does not worsen the depressive or other psychiatric symptoms in CHC patients with pre-existing mental diseases. Other studies, differently, feature the possible onset of mood symptoms in patients with psychiatric history [15][16][17].…”
Section: Discussionmentioning
confidence: 99%